The Role of Speech Therapy in Enhancing Communication Skills of Children with Exceptional Needs: A Critical Analysis - Ghasemzadeh, Azizreza; Saadat, Maryam; Kia Kojori, Razie (Psychological Research in Individuals with Exceptional Needs, 2024)
This article critically analyzes the role of speech therapy in enhancing the communication skills of children with exceptional needs. It explores the multifaceted nature of speech therapy, encompassing a range of interventions tailored to individual needs. The discussion includes the benefits of speech therapy, such as improvements in speech production, language abilities, social communication, and pragmatic language skills. Challenges and limitations within the field are also examined, along with a comparative analysis of speech therapy against other interventions. Current trends, latest developments, and research gaps in speech therapy are addressed, emphasizing the need for continued research and innovation. The article concludes with policy recommendations and practical implications for evidence-based speech therapy practices, highlighting their significance in promoting holistic development and well-being in children with exceptional needs.Keywords: Speech Therapy, Communication Skills, Children with Exceptional Needs, Critical Analysis.